Speech text of signing ceremony memorandum of understanding between Universiti Teknologi MARA and Corporate Secretaries International Association Limited (CSIA) Hong Kong / Prof. Datuk Dr. Shahrin Sahib @ Sahibuddin - Sahib @ Sahibuddin, Shahrin (2023)
Alhamdulillah, praise be to Allah S.W.T for His abundant blessings and the opportunity to gather here today for a momentous occasion for UiTM and its esteemed partner. 2. Allow me to extend a warm welcome and Selamat Datang to everyone in attendance for the Signing Ceremony of the Memorandum of Understanding between the Corporate Secretaries International Association Limited (CSIA) Hong Kong and Universiti Teknologi MARA (UiTM).